A New Generation of Fast and Low-Memory Smart Digital/Geometrical Beamforming MIMO Antenna - Pirapaharan, K.; Prabhashana, W.H.S.; Pramuka Medaranga, S.P.; Hoole, P.R.P.; Fernando, X. (MDPI, 2023)
Smart multiple-input multiple-output (MIMO) antennas with advanced signal processing algorithms are necessary in future wireless networks, such as 6G and beyond, for accurate space division multiplexing and beamforming. Such a MIMO antenna will yield better network coverage and tracking. This paper presents a smart MIMO antenna conﬁguration with a highly innovative beamforming technique using several nonlinear conﬁgurations of dipole arrays. Phase delay factors are optimized at the transmitter to form a single beam and then to steer the beam towards a particular direction. A number of phase shifters are added in order to obtain maximum directional gain. This conﬁguration also signiﬁcantly increases the power gain of the MIMO antenna at a low cost and with operational simplicity. The paper also demonstrates how the beam width and beamsteering can be effectively controlled. Wolfram Mathematica software was used to generate the three-dimensional radiated beam patterns of the transmitter antenna. There are two approaches to conﬁgure the receiver antenna. In the ﬁrst approach, the received signal magnitude is maximized by aligning the contribution of all elements of the receiver antenna to the same phase. With this approach, the ﬁeld gain of the proposed system is 25.52 (14.07 dBi). The signal processing gain at the receiver is 64 (18.06 dBi). Therefore, the overall power gain for this proposed new digital/geometrical smart MIMO system is 32.13 dBi. In the second approach, the receiver beam is directed towards the transmitter by optimizing the phase delay coefﬁcients of the receiver. Here, the overall gain of the system is found to be 134.56 (21.28 dBi). Even though the system gain in the second approach is lower, it has the advantage of low interference at the receiver side.
Keywords: MIMO systems; Smart antennas; Phase shifters; Beamforming; Beamsteering